1951
DOI: 10.1029/tr032i003p00443
|View full text |Cite
|
Sign up to set email alerts
|

Porosity factor for case of laminar flow through granular media

Abstract: The resistance coefficient of flow through granular media depends on the porosity of the medium as well as the Reynolds number of the flow. There is disagreement as to the functional relationship between porosity and resistance coefficient, hence a series of carefully conducted permeability tests was made on randomly packed and systematically packed media using a variable head permeameter. The test results indicated that the relationship between porosity and resistance coefficient for laminar flow through gran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1971
1971
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…According to Frank Engelund (1953) [34], this porosity function f L of the linear expression fits better than the function f L from Ergun Equation ( 23) to the measurements obtained by Rose (1953) [37] and Franzini (1951) [38], especially the latter, who worked with a wide interval of porosities 0.270 < n < 0.476. Ergun (1952) [12] proposed universal values for the dimensionless coefficients α and β.…”
Section: Resistance Formulas Based On the Representative Diameter Of The Particlesmentioning
confidence: 97%
“…According to Frank Engelund (1953) [34], this porosity function f L of the linear expression fits better than the function f L from Ergun Equation ( 23) to the measurements obtained by Rose (1953) [37] and Franzini (1951) [38], especially the latter, who worked with a wide interval of porosities 0.270 < n < 0.476. Ergun (1952) [12] proposed universal values for the dimensionless coefficients α and β.…”
Section: Resistance Formulas Based On the Representative Diameter Of The Particlesmentioning
confidence: 97%
“…The model shown in Equation (1) has been found valid for a large number of soils (Franzini, 1951;Lambe and Whitman, 1969;Taylor, 1948). Sridharan and Nagaraj (2005) studied this model by a number of tests and found that x = 4 and C = 2.5 x 10 -4 (I S ) -3.69 , where I S is shrinkage index = LL-SL.…”
Section: Introductionmentioning
confidence: 99%